THE EFFECTIVENESS OF RESILIENCY TRAINING TO IMPROVE FAMILY WELL-BEING AMONG WOMEN EXPERIENCED SEXUAL VIOLENCE IN ACEH - Eka - Srimulyani; Miftahul Jannah; Ida Fitria; Fatmawati Fatmawati; Rawdhah Binti Yasa; Iyulen Pebry Zuanny (State Islamic University (UIN) Ar-Raniry, 2021)
Sexual harassment has many negative impacts on the victims, both physically and psychologically. Women as victims of sexual harassment feel difficulties when they interact in social environment. The psychological impact on the victim will result in prolonged trauma and depression which can then lead to unhealthy attitudes such as insecurity, excessive fear, and disturbed mental conditions. For this reason, this study aimed to examine the effectiveness of resiliency training to improve family well-being among women victims of sexual violence in Aceh. The number of participants recruited were 7 women who have experienced sexual violence in PSAA Aceh. The research design used a one group pretest-posttest design and the data were collected using family well-being scale. The results of data analysis indicated that the provision of resiliency training did not have a significant contribution on increasing family well-being. This could be explained because the incidents of sexual violence experienced by the subjects have happened several years ago, so they have adapted to their families to the presence of children born from the sexual violence.